(untitled) (Research, Society and Development, 2025)
The increasing use of glucagon-like peptide-1 receptor analogs (GLP-1RAs) in the treatment of obesity and associated comorbidities has generated interest in evaluating their adverse effects, particularly gastrointestinal ones. In this context, the present study aims to analyze the adverse effects associated with the use of GLP-1 receptor analogs (GLP-1RAs), based on a systematic review of clinical studies. This was a systematic literature review, with data search conducted in the PUBMED, LILACS, and SCIELO databases. Initially, 1,696 articles were identified in the initial search, and after evaluating titles and abstracts, followed by the selection and detailed analysis of the articles, 11 studies were deemed eligible to be included in this systematic review. The total sample comprised approximately 23,596 individuals. There was a predominance of female participants in most of the studies, and the age range of the participants varied on average from 14.6 to 69 years. The most common and frequent adverse effects were, for the most part, mild to moderate, such as gastrointestinal symptoms, including nausea, vomiting, diarrhea, constipation, among others. However, some studies also identified severe adverse effects in certain patients, highlighting the need for clinical monitoring during treatment. In conclusion, although GLP-1 analogs offer significant clinical benefits, continuous patient monitoring is essential to manage adverse effects, ensuring safety and long-term adherence to treatment.